Cardiovascular disease in Europe 2014: epidemiological update. (19th August 2014) - Nichols, Melanie; Townsend, Nick; Scarborough, Peter; Rayner, Mike
Abstract: This paper provides an update for 2014 on the burden of cardiovascular disease (CVD), and in particular coronary heart disease (CHD) and stroke, across the countries of Europe. Cardiovascular disease causes more deaths among Europeans than any other condition, and in many countries still causes more than twice as many deaths as cancer. There is clear evidence in most countries with available data that mortality and case-fatality rates from CHD and stroke have decreased substantially over the last 5–10 years but at differing rates. The differing recent trends have therefore led to increasing inequalities in the burden of CVD between countries. For some Eastern European countries, including Russia and Ukraine, the mortality rate for CHD for 55–60 year olds is greater than the equivalent rate in France for people 20 years older.